Psychotropic drugs and pregnancy - J Pitanupong (Journal of Health Science and Medical Research (JHSMR), 2003)
Use of psychotropic drugs in pregnancy is common. Psychotropic drugs can pass across the placenta and have the potential for teratogenicity and neonatal effects. There is little data on the newer drugs so the lowest risk in the first trimester would appear to be to use the high-potency antipsychotic drugs, clozapine,nortriptyline and fluoxetine. Fluoxetine may cause low birth weight. Lithium, carbamazepine and valproic acid are associated with congenital malformation, especially Ebstien’s anomaly and neural tube defect, so they are contraindicated in pregnancy. A review of the treatments for anxiety has shown a higher incidence of teratogenicity in women taking benzodiazepines, so shorter-acting benzodiazepines may be acceptable later in pregnancy, but should be avoided if possible in the first trimester.